Improving Students Speaking Skill by Using Multi-Flow Map at the Tenth Grade of Students Man 5 Jombang - SEPTIAN RAGIL ANANDITA (Universitas KH. A. Wahab Hasbullah, 2019)
The objective of this study is to examine; the method that used in this research is communicative language teaching the media that used in this research is multi-flow map. The research design of this research is Classroom Action Research. This design was used because it was appropriate design to solve the problem that happened in the class. The result of the first cycle is failed because of students’ interaction were less optimal. So the writer decides to go to the second cycle, in this cycle the writer use more interesting media and the writer as the teacher more communicative during the class. The improvement of students’ speaking skill can be seen from the increase of their individual score from preliminary study to Cycle 2. The score of the speaking skill test showed that 19 of the students reached the target gain score. The improvement on the speaking skill covered the component of pronunciation, grammar, vocabulary and fluency. Dealing with the students’ interaction in the teaching and learning process, the analysis of observation showed positive results in that the students were enthusiastic and actively during in speaking. Finally, the implementation of Multi-flow Map to improve students speaking skill in the two Cycles was successfully.